2016
DOI: 10.4172/2155-9554.1000349
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Drivers and Clinical Features of Human Scabies at the Mfou Principal Prison, Centre Region of Cameroon

Abstract: Background and aim: Researches assessing the prevalence and magnitude of human scabies (HS) in Cameroonian penitentiaries are direly rare. The present study aimed to determine the prevalence, drivers and clinical features of HS in a Cameroonian prison.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“… Confounding factors identified Strategies to deal with confounding factors stated Outcomes measured in a valid and reliable way Was appropriate statistical analysis used? Total score( n = 8) Kouotou, EA [ 44 ] Yes Yes Yes Yes Yes Yes Yes Yes 8 Bartosik, K [ 45 ] Yes Yes Yes Yes No No Yes Yes 6 Bogino, E [ 46 ] Yes Yes Yes Yes Yes Yes Yes Yes 8 RAHMATI, R [ 47 ] Yes Yes Yes Yes Yes Yes Yes Yes 8 Mannocci, A [ 35 ] Yes Yes Yes Yes Yes Yes Yes Yes 8 Harouna, M [ 48 ] Yes Yes …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“… Confounding factors identified Strategies to deal with confounding factors stated Outcomes measured in a valid and reliable way Was appropriate statistical analysis used? Total score( n = 8) Kouotou, EA [ 44 ] Yes Yes Yes Yes Yes Yes Yes Yes 8 Bartosik, K [ 45 ] Yes Yes Yes Yes No No Yes Yes 6 Bogino, E [ 46 ] Yes Yes Yes Yes Yes Yes Yes Yes 8 RAHMATI, R [ 47 ] Yes Yes Yes Yes Yes Yes Yes Yes 8 Mannocci, A [ 35 ] Yes Yes Yes Yes Yes Yes Yes Yes 8 Harouna, M [ 48 ] Yes Yes …”
Section: Methodsmentioning
confidence: 99%
“…This systematic review also found that hygienic practices were significantly associated with the occurrence of scabies among prisoners, based on included studies [ 44 , 46 , 48 ]. Based on a study conducted in Ethiopia [ 46 ], prisoners who did not use soap during hand washing had 5.53 times [AOR = 5.53; 95% CI: 1.45–21.17] higher odds of exhibiting scabies.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations